2004
DOI: 10.1001/archderm.140.8.955
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of the 308-nm Excimer Laser for Pigment Correction of Hypopigmented Scars and Striae Alba

Abstract: To assess the safety and efficacy of the 308-nm excimer laser in pigment correction of hypopigmented scars and striae alba.Design: Institutional review board-approved randomized controlled trial.Setting: Private research center.Patients: Volunteer sample of 31 adult subjects with hypopigmented scars or striae alba distributed on the face, torso, or extremities.Interventions: Lesions were randomized to receive treatment or not, with site-matched normal control areas. Treatments were initiated with a minimal ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 31 publications
0
47
0
3
Order By: Relevance
“…34 AlexiadesArmenakas et al also indicated that following treatment with the 308-nm excimer laser, the percentage of pigment correction increased in direct correlation with the number of treatment sessions. 35 In a recent study, Wang et al compared the safety and efficacy of a 1540-nm and 1410-nm non-ablative fractional laser in treatment of striae, histologically and clinically. Both methods resulted in clinical and histological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…34 AlexiadesArmenakas et al also indicated that following treatment with the 308-nm excimer laser, the percentage of pigment correction increased in direct correlation with the number of treatment sessions. 35 In a recent study, Wang et al compared the safety and efficacy of a 1540-nm and 1410-nm non-ablative fractional laser in treatment of striae, histologically and clinically. Both methods resulted in clinical and histological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The 585-nm flash-pumped laser decreases erythema of early-stage lesions, 86 and the 308-nm excimer laser improves hypopigmentation associated with late-stage striae. 87,88 Striae rubra and alba have been treated with a pulsed dye laser with marginal success. 38 Laser therapy should be avoided for striae in individuals having Fitzpatrick skin types IV through VI because of the resultant hyperpigmentation.…”
Section: Hyperandrogenism and Hirsutismmentioning
confidence: 99%
“…A randomized controlled trial demonstrated pigment correction of hypopigmented scars and striae alba following 308-nm excimer laser therapy, with pigment increases correlating directly with the number of treatments (23). In addition, two case reports of excimer laser therapy have shown promise in the treatment of alopecia areata (24).…”
Section: Additional Applications Of Targeted Uv Therapymentioning
confidence: 99%